2005
DOI: 10.21273/horttech.15.4.0859
|View full text |Cite
|
Sign up to set email alerts
|

Remote Sensing of Shaded Area in Vineyards

Abstract: Airborne multispectral image data were compared with intercepted photosynthetic photon flux (PPF) in commercial winegrape (Vitis vinifera) vineyards of Napa Valley, Calif. An empirically based calibration was applied to transform raw image pixel values to surface reflectance. Reflectance data from the red and near-infrared spectral regions were combined into a normalized difference vegetation index. Strong linear response was observed between the ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…Average final plant populations and standard errors for sparse, typical, and dense subplots were 89 ±4, 164 ±3, and 291 ±10 plants m -2 for -2004, respectively. For 2004-2005, they averaged 79 ±4, 156 ±4, and 305 ±10 plants m -2 , respectively.…”
Section: Wheat Planting Post-plant Operations and Crop Emergencementioning
confidence: 98%
See 1 more Smart Citation
“…Average final plant populations and standard errors for sparse, typical, and dense subplots were 89 ±4, 164 ±3, and 291 ±10 plants m -2 for -2004, respectively. For 2004-2005, they averaged 79 ±4, 156 ±4, and 305 ±10 plants m -2 , respectively.…”
Section: Wheat Planting Post-plant Operations and Crop Emergencementioning
confidence: 98%
“…Over the years, remote sensing scientists have clearly established relationships between various multispectral vegetation indices (VIs), such as the normalized difference vegetation index (NDVI), derived from optical visible and near-infrared data, and various biophysical aspects of vegetation canopies, such as leaf area index (Moran et al, 1995), crop yield (Plant et al, 2000), and percent crop cover (Heilman et al, 1982). Additional research has shown that the multispectral VIs can provide realtime surrogates of crop coefficients for a variety of crops (Bausch, 1995;Neale et al, 2003;Hunsaker et al, 2005a;Johnson and Scholasch, 2005). Therefore, VIs obtained with remote sensing data potentially offer a means to infer in near real-time the spatial distribution of K cb across the landscape of a local field or on a broader farm-scale basis.…”
mentioning
confidence: 99%
“…For each acquisition date, images were captured under clear skies near solar noon to minimize the effect of shadowing between the vine rows. 40,41 Images were captured using a Hawkeye UAV platform (Kingsland, Texas, USA) 42 and two digital cameras. The Hawkeye is a battery-powered (electric) kitewing plane with a single propeller and a payload of ∼400 g. The Hawkeye used in this study had autopilot functionality (Ardupilot) 43 that, when enabled automatically, navigated to preprogrammed waypoints (X,Y,Z) using an on-board global positioning system (GPS) receiver.…”
Section: Uav Image Collectionmentioning
confidence: 99%
“…Previous studies have shown that various spectral vegetation indices, calculated from visible and near-infrared (NIR) reflectance data, are linearly related to the amount of photosynthetically active radiation absorbed by plant canopies (Asrar et al, 1984;Daughtry et al, 1992;Goward and Huemmrich, 1992;Johnson and Scholasch, 2005). Spectral indices such as the normalized difference vegetation index (NDVI), derived as the ratio of the difference and sum of reflectance in the NIR and red spectral regions, can effectively track spatially variable crop canopy development for particular crops in real time.…”
mentioning
confidence: 99%